Wellness, social policy and public health : bridging human flourishing with equity - Maturo, Antonio; Setiffi, Francesca (Emerald points., 2022)
A self-help buzzword, a sociological concept, and a target for political institutions; 'wellness' can be interpreted in different ways. It is viewed as a heterogeneous set of activities aimed at increasing both physical and mental individual well-being, including maintaining a healthy diet and lifestyle, being physically active and taking care of mental health. From a sociological perspective, 'wellness' can raise problematic issues; the pursuit of wellness activities is inherently affected by social and economic factors and social determinants, and the individual nature of the pursuit of wellness means it is not strongly related to community empowerment, the production of social capital and social cohesion. Wellness, Social Policy and Public Health: Bridging Human Flourishing with Equity considers wellness as an ecosystem instead of an activity to be carried out by an individual. Case studies explore current welfare policy and its relationship with wellness activities, demonstrating that individual flourishing related to wellness is activated only in a context of solid welfare infrastructures.